2017
DOI: 10.1590/0001-3765201720170199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anaerobic threshold in non-pregnant and pregnant rats

Abstract: Several studies present different methodologies and results about intensity exercise, and many of them are performed in male rats. However, the impact of different type, intensity, frequency and duration of exercise on female rats needs more investigation. From the analysis of blood lactate concentration during lactate minimum test (LacMin) in the swimming exercise, the anaerobic threshold (AT) was identified, which parameter is defined as the transition point between aerobic and anaerobic metabolism. LacMin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Since we used a standardized RAMP protocol in both groups, the ventilatory threshold occurred at lower cycle load levels during pregnancy. This is a new finding in human studies, but has been reported earlier in pregnant rats, which also reached their ventilatory threshold at lower exercise intensity levels (Netto et al, 2017). This suggests that during pregnancy, either the aerobic system is used less efficiently or the aerobic system is already used at higher levels during rest, which fits the hypothesis that pregnancy can be considered as a 24-hr/9-month lasting mild to moderate exercise.…”
Section: Discussionsupporting
confidence: 78%
“…Since we used a standardized RAMP protocol in both groups, the ventilatory threshold occurred at lower cycle load levels during pregnancy. This is a new finding in human studies, but has been reported earlier in pregnant rats, which also reached their ventilatory threshold at lower exercise intensity levels (Netto et al, 2017). This suggests that during pregnancy, either the aerobic system is used less efficiently or the aerobic system is already used at higher levels during rest, which fits the hypothesis that pregnancy can be considered as a 24-hr/9-month lasting mild to moderate exercise.…”
Section: Discussionsupporting
confidence: 78%
“…The pregnant rats were submitted to 0%, 20%, 80% and 140% of the anaerobic threshold (AT) for the swimming practice. In previous study (Netto et al 2017), the AT of the pregnant rats was identified in minimum load of 5% of the body weight. Then, for this investigation the pregnant rats were distributed into four experimental groups (n = 13 animals/group) -1) Control: Not exercise group -no load (0% of AT); 2) Mild-exercise intensity: with 20% of AT, which corresponded to 1% of body weight of each rat; 3) Moderate-exercise intensity: with 80% of AT, which corresponded to 4% of body weight; 4) Heavy-exercise intensity: with 140% of AT, equivalent to 7% of body weight.…”
Section: Mating Procedures and Experimental Groupsmentioning
confidence: 99%
“…The exercise was held in the morning for 30 minutes daily. The rats were subjected to swimming from day 7 to day 20 of pregnancy (Netto et al 2017). An appropriate control with sedentary rats was made with the same time of exposure to water.…”
Section: Physical Exercise -Swimming Programmentioning
confidence: 99%